D’une charte l’autre : le processus de révision de la charte des AMAP comme indicateur d’une institution qui se renforce - Claire Lamine; Juliette Rouchier (Revue de la Régulation)
In this paper we describe the evolution of AMAP institution (french CSA) when the revision process of the Charter took place (2013) - a text that has to be signed to be allowed to use the name AMAP. Analyzing the evolution of contents of the documents as well as the innovative revision process, we show that a constitutional level was added. This resolved some tensions, but also completed the system of rules of the institution (Ostrom, 1990), and thus must have made this exchange system more durable.